Effect of flexible fibers on rheological properties of poly(Lactic Acid) composites under elongational flow - Yamaguchi, Masayuki; Yokohara , Tadashi; Md Ali , Mohd Amran (2013)
Rheological properties of polymer composites with flexible fine fibers are studied employing poly(lactic acid) PLA containing a small amount of polymeric fibers of PTFE, PBT and PMP.